2020
DOI: 10.1093/humrep/deaa124
|View full text |Cite
|
Sign up to set email alerts
|

Type of menopause, age of menopause and variations in the risk of incident cardiovascular disease: pooled analysis of individual data from 10 international studies

Abstract: STUDY QUESTION How does the risk of cardiovascular disease (CVD) vary with type and age of menopause? SUMMARY ANSWER Earlier surgical menopause (e.g. <45 years) poses additional increased risk of incident CVD events, compared to women with natural menopause at the same age, and HRT use reduced the risk of CVD in women with early surgical menopause. WHAT IS KNOWN ALREADY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 45 publications
2
56
0
Order By: Relevance
“…However, this result needs to be interpreted with caution since CLSA does not have information about the age at hysterectomy, and as suggested in the InterLACE study the age of surgical menopause may modify the effect of HT on the FRS. 7 …”
Section: Discussionmentioning
confidence: 99%
“…However, this result needs to be interpreted with caution since CLSA does not have information about the age at hysterectomy, and as suggested in the InterLACE study the age of surgical menopause may modify the effect of HT on the FRS. 7 …”
Section: Discussionmentioning
confidence: 99%
“…Androgen replacement may be considered for women with persistent fatigue and loss of libido, in spite of estrogen replacement. Counsel women that HT is not a contraceptive, and erratic ovulation and pregnancy may occur in POI There is no evidence that HT increases risk of breast cancer, CVD, or dementia, over and above that found in menstruating women with a normally timed menopause Women with untreated premature menopause are at increased risk of developing osteoporosis, CVD, dementia, cognitive decline, and Parkinson's and all-cause mortality[ 127 128 129 ] Women receiving chemotherapy or radiotherapy (pelvis) should be cautioned about iatrogenic premature menopause Premenopausal hysterectomy alone may cause early menopause[ 130 131 ] …”
Section: A Bnormal M Enopausementioning
confidence: 99%
“…Women with untreated premature menopause are at increased risk of developing osteoporosis, CVD, dementia, cognitive decline, and Parkinson's and all-cause mortality[ 127 128 129 ]…”
Section: A Bnormal M Enopausementioning
confidence: 99%
“…Our findings align with other large-scale epidemiologic studies of early menopause and cardio-cerebrovascular diseases [12,28], which reported that early menopause had a significantly higher risk of developing cardiovascular disease and stroke than natural menopause. Furthermore, not only the type of menopause but also the time since onset of menopause has been reported as a factor affecting the occurrence of CAD and cardiovascular diseases [8,10,18]. Meta-analysis showed that women with higher age of menopause and shorter periods of time after the onset of menopause had a relatively low risk of CAD [8,18].…”
Section: Discussionmentioning
confidence: 99%
“…We identified certain sociodemographic, lifestyle, and healthrelated factors as risk factors for cardio-cerebrovascular diseases based on previous studies [9,17,18]. The sociodemographic factors included age, education, and monthly income.…”
Section: Risk Factors Of Cardio-cerebrovascular Diseasesmentioning
confidence: 99%